Alveolar soft part sarcoma in childhood and adolescence: Report of three cases and review of literature - Zhang, Yudi; Wang, Ying; Wang, Hao; Wen, Chuan; Wu, Xiaochuan (Frontiers in Pediatrics, 2022)
Alveolar soft part sarcoma (ASPS) is a rare soft tissue sarcoma with unique tumor characteristics, which is rare in children. Herein, we present the immunophenotype, treatment, and prognosis of three children with ASPS from The Second Xiangya Hospital of Central South University, and 51 children with ASPS have been reported in the previous literature, along with a focused review of the clinical features, pathological features, differential diagnosis, treatment, and prognosis of ASPS in pediatric patients.